Osteoplastic decompressive craniotomy--an alternative to decompressive craniectomy - Mracek, Jan; Choc, Milan; Mork, Jan; Vacek, Petr; Mracek, Zdenek (Acta neurochirurgica, 2011)
BACKGROUND: In spite of various degrees of brain expansion, decompressive surgery is usually carried out using decompressive craniectomy (DC). After craniectomy it is necessary to perform cranioplasty, which prolongs hospitalization and is not always without complications. Hence, in situations when cranial decompression is indicated, but DC would be too radical, we do not remove the bone flap, and we perform so-called osteoplastic decompressive craniotomy (ODC). The technique is detailed. OBJECTIVE: To demonstrate the effectiveness of ODC. METHODS: Twenty patients underwent ODC for brain edema under various pathological conditions. The diagnoses were as follows: 13 subdural hematomas, 3 cerebral contusions, 2 middle cerebral artery infarcts, 1 epidural hematoma and 1 arteriovenous malformation. The effect of ODC was assessed using postoperative ICP monitoring and the midline shift on CT. The ICP threshold for the additional removal of the bone flap was 25 mmHg. Clinical outcome was evaluated 6 months after surgery using the Glasgow Outcome Scale (GOS). RESULTS: Postoperative ICP was up to 25 mmHg in 18 patients and exceeded 25 mmHg in 2 cases. The mean midline shift on CT was 10 mm preoperatively and 3 mm postoperatively. The decompression during ODC was sufficient in 18 patients and insufficient in 2 in whom an additional removal of the bone flap was performed. Eight survivals had a favorable outcome (GOS 4-5); 12 patients had an unfavorable outcome (GOS 1-3), and of these, 4 died. CONCLUSION: Our limited study shows that ODC is effective in the treatment of intracranial hypertension in the selected subgroup of patients in whom DC would be too radical. The main advantage of this method is the elimination of further cranioplasty.
Keywords: dospělí; Female; radiografie; dítě; Radiography; dekompresní kraniektomie; Adult; mladý dospělý; ženské pohlaví; dura mater; lidé; pooperační komplikace; Brain Diseases; Middle Aged; Skull; retrospektivní studie; Male; Postoperative Complications; Aged; Dura Mater; nemoci mozku; Young Adult; lidé středního věku; lebka; Child; Craniotomy; senioři; mužské pohlaví; Decompressive Craniectomy; Retrospective Studies; kraniotomie; Humans